Gut microbiota and cardiovascular risk factors. Part IV. Arterial hypertension, smoking and the gut microbiota - D. A. Kashtanova; O. N. Tkacheva; S. A. Boytsov (Кардиоваскулярная терапия и профилактика, 2016)
The collected data on the interaction of human-as-host and their gut microbiota reveals new opportunities for further investigation and translation to practice the novel methods of the body influence in whole and on separate systems, particularly via correction of gut microbiota condition. Previous reviews focused on recent data on the interaction of gut microbiota with the main cariovascular risk factors. Last article in this sequel focuses on the recent data on hypertension and condition of the gut microbiota, as on the influence of smoking on the gut microbiota. The article presents the results of investigations on the influence of short-chain fatty acids on arterial pressure, and on smoking impact on the gut microbiota.